2021
DOI: 10.1024/1422-4917/a000844
|View full text |Cite
|
Sign up to set email alerts
|

School Entry Plays an Insignificant Role in Attention Performance, Impulse Control, and Motor Activity of Same-Aged Children from Preschool and Elementary School

Abstract: Abstract. The transition from preschool to elementary school places demands on children to pay attention, control their impulses, and avoid fidgeting. However, to the best of our knowledge, no studies have investigated whether these characteristics are influenced by elementary school entry. The current study compares same-aged preschool and elementary-school children regarding their attention performance, impulse control, and motor activity. A total of 60 children (30 preschool and 30 elementary school; 6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Commission error showed a low effect size in the study probably because this measure has lower sensitivity for adults with ADHD compared to children. In earlier studies, higher rates of Commission Error were found in children compared to adolescents and adults [ 36 , 40 , 42 ]. Pettersson et al, found that only the cardinal parameters QbActivity and QbInattention were significant predictors of clinical diagnosis in adult ADHD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commission error showed a low effect size in the study probably because this measure has lower sensitivity for adults with ADHD compared to children. In earlier studies, higher rates of Commission Error were found in children compared to adolescents and adults [ 36 , 40 , 42 ]. Pettersson et al, found that only the cardinal parameters QbActivity and QbInattention were significant predictors of clinical diagnosis in adult ADHD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%